Genomic insight into pathogenicity of dematiaceous fungusCorynespora cassiicola - Looi, H.K.; Toh, Y.F.; Yew, S.M.; Na, S.L.; Tan, Y.C.; Chong, P.S.; Khoo, J.S.; Yee, W.Y.; Ng, K.P.; Kuan, C.S. (PeerJ, 2017)
Corynespora cassiicola is a common plant pathogen that causes leaf spot disease in a broad range of crop, and it heavily affect rubber trees in Malaysia (Hsueh, 2011; Nghia et al., 2008). The isolation ofUM591 from a patient's contact lens indicates the pathogenic potential of this dematiaceous fungus in human. However, the underlying factors that contribute to the opportunistic cross-infection have not been fully studied. We employed genome sequencing and gene homology annotations in attempt to identify these factors in UM 591 using data obtained from publicly available bioinformatics databases. The assembly size ofUM591 genome is 41.8 Mbp, and a total of 13,531 (≥99 bp) genes have been predicted. UM591 is enriched with genes that encode for glycoside hydrolases, carbohydrate esterases, auxiliary activity enzymes and cell wall degrading enzymes. Virulent genes comprising of CAZymes, peptidases, and hypervirulenceassociated cutinases were found to be present in the fungal genome. Comparative analysis result shows that UM 591 possesses higher number of carbohydrate esterases family 10 (CE10) CAZymes compared to other species of fungi in this study, and these enzymes hydrolyses wide range of carbohydrate and non-carbohydrate substrates. Putative melanin, siderophore, ent -kaurene, and lycopene biosynthesis gene clusters are predicted, and these gene clusters denote that UM 591 are capable of protecting itself from the UV and chemical stresses, allowing it to adapt to different environment. Putative sterigmatocystin, HC-toxin, cercosporin, and gliotoxin biosynthesis gene cluster are predicted. This finding have highlighted the necrotrophic and invasive nature of UM 591.